Plant parameters and must composition of ‘Syrah’ grapevine cultivated under sequential summer and winter growing seasons - Pedro Júnior,Mário José (2017)
ABSTRACT Plant variables and must physicochemical properties were evaluated for the grapevine ‘Syrah’ cultivated in sequential growing seasons (summer and winter) from 2011 to 2015. The vines were trellised in vertical shoot position, grafted on Paulsen 1103, with approximate density of 5,800 plants∙ha−1. They were grown under plastic overhead cover. The experimental design was completely randomized, and the following variables were measured at the harvest: number of branches, number of clusters, cluster weight and yield, soluble solids content, pH, and titratable acidity. The highest values of yield, cluster weight, and titratable acidity were observed during the summer growing season, while the highest values of soluble solids content and pH were observed during winter. These results suggest that the grapes harvested during the winter show physicochemical characteristics more suitable than those observed during the summer crops for winemaking purposes.